Designing A Web-Based Credit Application Information System: Study at One of The Sharia Financial Institutions in Bandung - Hani Supriati; Haris Supriatna (P3M, STIE Pasundan, Bandung, Indonesia., 2023)
In today's technological developments, the role of Internet media must be addressed. The ease of doing online activities certainly must be connected to the critical role of websites in it. One of the benefits of applying the Internet in the banking sector is simplifying work processes such as processing data for credit applications. The system being used to process data at one of the Sharia financial institutions in Bandung still needs to be better organized, so it is less effective and efficient, less accurate, or errors often occur, and also takes up much space for customer documents. Therefore, the author is interested in building a system expected to overcome the problems faced by one of the Sharia financial institutions in Bandung. This system was formulated as